(untitled) (Bioagro, 2024)
The identification of phytoparasitic nematodes, which is essential for the implementation of management strategies, is required for further study. The objective of this work was to identify, at the genus level, the phytoparasites and free-living nematodes associated with the cultivation of sweet granadilla (Passiflora ligularis Juss.) in the valley of Sandia, region Puno, Peru. For the study, 165 soil samples were evaluated, coming from eight communities from the district of Sandia, during the agricultural season 2018–2019. The samples were processed by the method of centrifugal fluctuation in sucrose solution, later identified on the basis of morphological characteristics. The results showed the presence of seven genera of phytoparasitic nematodes, Meloidogyne, Pratylenchus, Helicotylenchus, Mesocriconema, Xiphinema, Tylenchus, and Hemicycliophora, and two genera of free-living nematodes, Aphelenchus and Dorylaimus. The most harmful genera were Meloidogyne and Pratylenchus because they cause damage to other crops. In the nematode community, there was variability in the density and frequency of phytoparasitic and free-living nematodes in the evaluated localities.